Methodological evaluation of gingival crevicular fluid volume and neutrophil elastase levels: sequential sampling, length of sampling time and two different sampling methods. (18th May 2020) - Kayar, Nezahat Arzu; Oduncuoğlu, Bahar Füsun; Haliloğlu, Seyfullah; Serpek, Behiç; Ataoğlu, Tamer; Alptekin, Nilgün Özlem
Abstract: Objectives: The mechanisms underlying the formation and composition of gingival crevicular fluid (GCF) and its flow into and from periodontal pockets are not understood very well. The aim of this study was to evaluate the length of sampling time and sequential sampling of GCF neutrophil elastase (NE) enzyme levels by using intracrevicular and orifice methods. Material and methods: Twenty adults (mean age of 41.8 years, ranged 31–60 years, 18 males and 2 females) with chronic periodontitis were enrolled and all completed the 3-d study. GCF was collected by both intracrevicular and intrasulcular methods, 720 samples of GCF were collected. In first, second and third day, the length of sampling time in seconds (s) and order were '5- 10-30-s'; '10- 30- 5-s' and '30- 5- 10-s, ' respectively. GCF elastase levels were determined by hydrolysis of neutrophil specific substrate N-methoxysuccinyl-Ala-Ala-Pro-Val-p-nitroanilide. Results: NE activity (µU) and NE activity/volume (µU/µl) were significantly different for order of sampling ( p  < .05), but not for the length of sampling time ( p >.05). Conclusions: Within the limits of this study, the choice of sampling technique in GCF-profile studies seems to be a critical decision as it has the potential to affect the GCF volume and NE activity.